Implementation of the NHT Type Cooperative Learning Model to Improve Mathematics Learning Outcomes - Hasibuan, Jose Bonatua; Wahyudin, Dinn (SUKMA: Jurnal Pendidikan, 2023)
At the Integrated Agricultural Vocational High School in Riau Province, there are many problems faced by students in the process of learning mathematics, including the lack of motivation to learn, students are less active in learning activities, students have difficulty mastering the material, and students' basic mathematical abilities are low, so this will also affect student learning outcomes. The results of the author's observations as a teacher in Class XII APHP 1 found that most students had difficulty solving math problems, so this had an effect on student learning outcomes that were not optimal. Researchers think that a learning model is needed that can activate students during teaching and learning activities. The learning model that is expected to encourage activeness, independence and responsibility in students is the NHT cooperative learning model. Through the application of the NHT type cooperative learning model, it is hoped that it can increase the learning activity of class XII APHP 1 students so that student learning outcomes will also increase.